O Curso de Bacharelado em Direito da UNIFAP: estratégias sobre o ensino das tecnologias com base nas diretrizes curriculares e o parecer Nº 757/2020 - Cavalheiro, Géssica Louhane Silva (2023)
The Rule No. 757 of 2020 published by the CNE - Conselho Nacional de Educação (National Education Council) amended article 5 of Resolution No. 5 of 2018, on December 18, 2018. The update law reorganizes that called by DCNs Diretrizes Nacionais Curriculares (National Curriculum Guidelines) for Law graduation in Brazil. The changes were necessary because the course needs to present its classes and content in an up-to-date manner. The Law course will enable students to have most new technical skills to work in that area. This research has the general objective of identifying the strategies applied by universities to implement the changes imposed by Rule 757/2020 and also subsequent norms, by teaching of the Law course at the UNIFAP Universidade Federal do Amapá (Federal University of Amapá). The provisions of the Federal Constitution and also by LDB Leis de Diretrizes e Bases da Educação (Law of Guidelines and Bases of Education), which it is exposed as a theoretical basis; presents bibliographical texts that define higher education and digital technologies, in addition to previous studies that contextualize the paper. This is an applied study with a qualitative approach. As for the another objectives, this research is classified as descriptive- exploratory. As for the technical data collection procedures, it is expost-facto and documentary research. The research population consists of twenty-eight professors and four managers of the Law School at the UNIFAP. It has a non-probabilistic and intentional sample, whose selection candidate will be: i) to be a professor and/or manager of the Bachelor of Law course at the Federal University of Amapá; and ii) that the participants are available to respond to the experimental, and that satisfactory information is sufficient for data analysis and research composition. It uses a personalized instrument for the actors involved, managers and professors of the Law School, as a data collection instrument. It was found that although the UNIFAP Law course curriculum is still in the process of updating the current Curricular Guidelines for the course, discussions about the new curriculum are ongoing and strategies for applying technologies are already beingapplied.